Respuestas
Respuesta dada por:
0
x + 3 = 2x
x - 2x = - 3
- 1x = - 3
x = -3/-1
x = 3 ⬅ Respuesta.
-------------------------------------------
x (x - 3) = 18
x^2 - 3x = 18
x^2 - 3x - 18 = 0
(x - 6) (x + 3)= 0
x - 6 = 0
x = 6 ⬅1 Respuesta
x + 3 = 0
x = - 3 ⬅2 Respuesta.
------------------------------------------
3x + 4x = 40
7x = 40
x = 40/7 ⬅Respuesta.
x - 2x = - 3
- 1x = - 3
x = -3/-1
x = 3 ⬅ Respuesta.
-------------------------------------------
x (x - 3) = 18
x^2 - 3x = 18
x^2 - 3x - 18 = 0
(x - 6) (x + 3)= 0
x - 6 = 0
x = 6 ⬅1 Respuesta
x + 3 = 0
x = - 3 ⬅2 Respuesta.
------------------------------------------
3x + 4x = 40
7x = 40
x = 40/7 ⬅Respuesta.
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años